A Novel Species of Penicillium With Inhibitory Effects Against Pyricularia oryzae and Fungal Pathogens Inducing Citrus Diseases - Liang, Li-Juan; Jeewon, Rajesh; Dhandevi, Pem; Durairajan, Siva Sundara Kumar; Li, Hongye; Lin, Fu-Cheng; Wang, Hong-Kai (Frontiers in Cellular and Infection Microbiology, 2021)
A novel species of Penicillium, proposed as P. linzhiense sp.nov was isolated from soil collected in Linzhi Town, Linzhi County, Tibet Autonomous Region, China. DNA sequence analyses from eight different gene regions indicate that the isolate represents a novel species and most closely related to P. janczewskii. The phylogenetic analysis based on a concatenated dataset of three genes, ITS, CaM, and BenA, also confirmed the placement of the novel species within the Canescentia section of the genus Penicillium. Differences in morphology among similar species are detailed and single gene phylogenies based on ITS, CaM and BenA genes as well as a multi-loci gene phylogeny are presented. Cultural studies were performed to study inhibitory activities on plant pathogens. The results reveal a notable antifungal activity against Pyricularia oryzae causing rice blast with an inhibition rate up to 77%, while for other three citrus pathogens, Diaporthe citri, Phyllosticta citrichinaensis, and Colletotrichum gloeosporioides, inhibition rate was 40, 50, and 55% respectively. No noticeable effects were observed for Fusarium graminearum, Botryosphaeria kuwatsukai, and Rhizoctonia solani. Interestingly, unlike other reported members of Canescentia, P. linzhiense showed no antagonistic effect on root rotting fungi. The new taxon isolated here has the potential to be used as a biocontrol agent especially for economically important phytopathogens or emerging pathogens on diseases occurring on citrus or rice.